The Concept and Implementation of Environment-Based Curriculum Management in Elementary School - Efi Tri Astuti; Haryanti Haryanti; Mika Andayani (Postgraduate Program Magister Pendidikan Agama Islam, 2021)
The curriculum is an important aspect of achieving educational goals. Education not only provides knowledge about the environment but also increases awareness and concern for environmental conditions. This research was conducted with the aim of describing the concept and application of environmentally sound curriculum management, supporting factors, inhibiting factors, and efforts to overcome them. This study uses a qualitative - descriptive approach, with a purposive sampling technique. Data was collected through interviews, documentation and literature study. The results showed that SD Alam Pacitan is a school that implements environmentally friendly curriculum management. That curriculum makes environmental elements the main object in the learning process to help characterize students. There are 4 stages carried out, that's are planning, implementation, monitoring, and evaluation. The inhibiting factors consist of the lack of facilities, infrastructure, and funding. The action to overcome this is the establishment of cooperation with many parties.